Rotation Effect on Jet Impingement Heat Transfer in Smooth Rectangular Channels with Film Coolant Extraction - James A. Parsons; Je-Chin Han (International Journal of Rotating Machinery)
The effect of channel rotation on jet impingement cooling by arrays of circular jets in twin channels was studied. Impinging jet flows were in the direction of rotation in one channel and opposite to the direction of rotation in the other channel. The jets impinged normally on the smooth, heated target wall in each channel. The spent air exited the channels through extraction holes in each target wall, which eliminates cross flow on other jets. Jet rotation numbers and jet Reynolds numbers varied from 0.0 to 0.0028 and 5000 to 10,000, respectively. For the target walls with jet flow in the direction of rotation (or opposite to the direction of rotation), as rotation number increases heat transfer decreases up to 25% (or 15%) as compared to corresponding results for non-rotating conditions. This is due to the changes in flow distribution and rotation induced Coriolis and centrifugal forces.